Multi‐taper spectrum‐based estimator for cognitive radio using multiple antennas and STBC techniques. Issue 2 (31st January 2018) - Abdul Salam, Ahmed O.; Sheriff, Ray E.; Al‐Araji, Saleh R.; Mezher, Kahtan; Nasir, Qassim
Abstract : An effective approach for the design of spectrum estimation (SE) in cognitive radio systems using multi‐taper method (MTM) and spatiotemporal features is presented in this study, whereas the MTM balances the bias‐variance dilemma, the multiple‐input–multiple‐output (MIMO) and space–time block code (STBC) are customarily aimed to defeat the adverse channel effects and enhance the system capacity and performance. The singular value decomposition is exploited to determine the dominant eigenchannels in MIMO and STBC setups. The maximum‐ratio combining, on the other hand, is adopted to produce higher signal‐to‐noise ratios usually intended for high data rates and reliability levels. The statistical analysis and modelling of the performance metrics associated with the SE based on MTM‐STBC and MIMO are approached using the quadratic form approximation. Simulation exercises are employed to compare this different SE, which will be called multitaper spectrum estimation (MTSE), against other typical methods such as the periodogram without tapering options. The results exhibit performance gains due to the merger of MTSE and STBC technologies over MIMO and periodogram SE (PSE) algorithms. Further computational analysis shows that the MTSE–STBC has no extra burdens compared with its PSE counterpart.